Edukasi Penggunaan Sediaan Body Scrub Menggunakan Ekstrak Etanol Daun Salam (Syzygium Polyanthum (Wight.) Walp) dan Serbuk Beras Putih (Oryza Sativa L.) sebagai Pelembap Kulit - Monica Suryani; Julia Susanti; Dumartina Hutauruk (jurnal ABDIMAS Indonesia, 2024)
Providing education to the public by using bay leaves as a preparation will increase public awareness of the plants that grow in Indonesia, which are rich in health benefits, thereby increasing public enthusiasm. Bay leaves combined with white rice powder are often used as a moisturizer so they are made into a body scrub preparation that can increase moisture into the skin for better. The aim of this service is that the community is expected to provide education about bay leaves and white rice powder in Klambir V Village, Medan, Indonesia. This community service method was carried out using leaflets, modules, power points and presentations to the community. The result of this service was an increase in public knowledge of tamarind fruit as an antioxidant by 85%..